PROTOTIPE PENGANGKAT SAMPAH OTOMATIS PADA SALURAN PINTU AIR BERBASIS MIKROKONTROLER ATMEGA 8535 - Kurniawan, Abdillah; Winarno, Heru (Vocational School Diponegoro University, 2013)
Abdillah Kurniawan, Heru Winarno, in paper prototype of waste lifting automatic on channel floodgate based on microcontroller ATMega 8535 explain that waste generated by the community from day to day more and more. Waste problems increasingly complex society is not discipline, in the sense that many people who throw garbage out of place, including dumped in the river. It can disrupt the flow of water. So in this thesis was designed prototype automatic garbage lifting the sluice channel driven by a 12 volt DC motor, used as a carrier conveyor trash removal results, this prototype design using microcontroller 8535 as the system controller. Minimum System 8535 microcontroller itself is as controller input, output, dc motor driver, rang the buzzer in case of opening the floodgates, and lcd M1632 as a viewer status. Trash removal tool aims to reduce the accumulation of garbage in the canal sluice. With these tools can mitigate human performance. Keywords: Microcontroller 8535, Lcd M1632, 12 Volt DC Motor, Buzzer